Attitudes to aging mediate the reciprocal effects of health anxiety and physical functioning. Issue 2 (1st February 2023) - Bodner, Ehud; Shrira, Amit; Palgi, Yuval
Abstract: Objective: To understand if attitudes to aging mediate the reciprocal effects of health anxiety and physical functioning among older adults with medical conditions. We examined: (1) if these effects are reciprocal; (2) if attitudes to aging (psychological loss, psychological growth, physical change) play a mediating role in these effects. Design: A sample of 226 community-dwelling older adults (T1 age range = 65-94, mean age = 73.59, SD = 6.29) reporting at least one chronic medical condition completed two phone interviews across six months. Main outcome measures: Background measures, health anxiety, physical functioning, and attitudes to aging at T1 and T2. Results: T2 attitudes to aging served as a mediator controlling for T1 attitudes. There was a direct effect of worse physical functioning at T1 on increased health anxieties at T2. Negative (but not positive) attitudes to aging mediated that effect. The reversed temporal sequencing (T1 health anxiety leading to T2 physical functioning) was significant only when mediated by negative attitudes to aging. Conclusions: Findings suggest that viewing aging as mostly a time of losses (but not as a time of gains) serves as an important mechanism through which health anxieties and physical functioning affect each other among older adults having chronic medical conditions.